ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT DKI JAKARTA DALAM TINJAUAN ABU YUSUF - Farestha Azra Faradila (2023)
Public financial management policies have existed since the time of the Prophet Muhammad, especially the concept of taxation and has developed over time because public financial management policies are inseparable from welfare. Many figures have contributed their thoughts, including Abu Yusuf. He has poured his thoughts in the Book of AL-Kharaj. So it is interesting to study how Abu Yusuf's thoughts in the Book of AL-Kharaj are to realize people's welfare. In this study, the author will implement Abu Yusuf's thoughts on the people of DKI Jakarta. DKI Jakarta is a province with the largest local tax revenue in Indonesia so that DKI Jakarta is an area with a fairly rapid economic growth rate. The method used is a qualitative method with a library research approach. The research found that there are three indicators of Abu Yusuf's thinking about welfare, namely the procurement of public infrastructure and facilities, a transparent financial system, and tax collection that does not burden the people, and there is relevance between Abu Yusuf's thoughts which have existed for centuries and the existing conditions. in DKI Jakarta today.